CHALLENGES AND STRATEGIES IN WRITING ENGLISH ACADEMIC PAPERS: A GRADUATE STUDENT’S SELF-REFLECTION - Dwi Ariyati; Anna Marietta da Silva (Sanata Dharma University Yogyakarta, 2025)
Writing academic papers in English is complex and daunting. However, many students are able to face the difficulties and find appropriate solutions to tackle the problems, one of which is through a self-reflection. This study aims at extending the literature by focusing on one student’s self-reflection that was carried out during the learning process in one academic writing class in a master’s program in Applied English Linguistics. The reflection centred upon the feedback given on all assignments given in the first half of the semester. The reflective notes were analysed qualitatively. Findings demonstrated that the participant’s most salient problems included incorporating the academic convention into her writing, understanding and using terminologies in Applied English Linguistics, and using appropriate syntax. To deal with the challenges, she used both direct and indirect language learning strategies, namely correcting her assignments based on the teacher’s feedback, communicating the writing problems with the teacher, writing other classroom papers in English directly, and making self-correction using an AI-based tool. The participant’s learning strategies were made on the basis of her self-efficacy beliefs and self-regulation. The study recommends the incorporation of self-reflection into academic writing class to develop students’ academic writing skills.